Perkembangan Bahasa Anak Usia Dini 5-6 Tahun Ditinjau dari Aspek Sintaksis dan Pragmatik - Arviani Sari (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to describe language acquisition in the field of syntax for children aged 5-6 years and describe language acquisition in pragmatics for children aged 5-6 years. This research uses descriptive qualitative research method. The sample of this study were two children aged 5-6 years Masyithoh Kindergarten Karangasem Batang. From the two samples, it is known that in the syntactic aspect, children experience different developments from the ability to tell stories, answer the phone, talk without stopping and speak in slang. In the pragmatic aspect, children also have developmental differences in terms of understanding sign language and interacting with sign language. Researchers concluded that early childhood in the age range of 5-6 years experienced differences in the development of syntactic and pragmatic language. So, the researcher recommends that teachers understand the differences in these developments and stimulate students according to their development so that they continue to improve.